The crosstalk between nerves and immunity: chronic stress as a driver of tumor progression - He, Yuan; Yu, Haoliang; Li, Fengze; Liu, Junzhe; Chen, Zhihao; Zhu, Wenping; Yang, Li; Yan, Tengfeng (Frontiers in Immunology, 2026)
Chronic stress, a sustained psychophysiological state, promotes tumor progression primarily by disrupting anti-tumor immunity. Through persistent activation of the HPA axis and sympathetic nervous system, stress hormones such as glucocorticoids and catecholamines reshape the tumor microenvironment and systemically impair immune surveillance. This leads to suppressed activity of cytotoxic lymphocytes, expansion of immunosuppressive cells, and ultimately, enhanced immune evasion and metastasis. Furthermore, these pathways undermine the efficacy of conventional and emerging therapies by fostering multidrug resistance. This review highlights these mechanisms and discusses the promise of targeting stress signaling, through both pharmacological and behavioral interventions, as a strategy to improve cancer outcomes. To address the current lack of clinical guidelines for counteracting the cancer progression mediated by chronic stress, this review propose a tiered screening and intervention model based on easily accessible biostress biomarkers. This hypothesis aims to bridge the gap between basic mechanism research and clinical application, providing a theoretical foundation directional guidance for future research.